Subarachnoid-Pleural Fistula: Applied Anatomy of the Thoracic Spinal Nerve Root. (13th July 2011) - Shamji, Mohammed F.; Sundaresan, Sudhir; Da Silva, Vasco; Seely, Jean; Shamji, Farid M.
Abstract : Subarachnoid-pleural fistula (SPF) is a rare complication of chest or spine operations for neoplastic disease. Concomitant dural and parietal pleural defects permit flow of cerebrospinal fluid into the pleural cavity or intrapleural air into the subarachnoid space. Dural injury recognized intraoperatively permits immediate repair, but unnoticed damage may cause postoperative pleural effusion, intracranial hypotension, meningitis, or pneumocephalus. We review two cases of SPF following surgical intervention for chest wall metastatic disease to motivate a detailed review of the anatomy of neural, osseous, and ligamentous structures at the intervertebral foramen. We further provide recommendations for avoidance and detection of such complication.